2023
DOI: 10.3389/fendo.2023.1165574
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal stem cells therapy improves ovarian function in premature ovarian failure: a systematic review and meta-analysis based on preclinical studies

Abstract: BackgroundStudies have revealed that the transplantation of mesenchymal stem cells (MSCs) might be a potential star candidate for premature ovarian failure (POF) in animal experiments. However, individual studies with a small sample size cannot be used to draw a clear conclusion. Therefore, we conducted a systematic review and meta-analysis to explore the potential of using MSCs in the treatment of POF in animals.MethodsSeven databases were searched for studies exploring the effect of the transplantation of MS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Although previous studies have demonstrated promising results regarding the ability of MSCs to facilitate the regeneration of bone, blood vessels, skin, peripheral nerves, and alleviate symptoms of local ischemia in various organs like the heart, kidneys, and brain, it is important to note that MSCs have been sometimes viewed as a panacea within the field of tissue repair and regenerative medicine [ 24 , 36 ]. Studies also showed that co-cultured of MSCs with follicles could promote follicle survival and development [ 30 , 31 , 37 ]. In the study, when we tried to reconstitute the ovarian structure with different concentrations of BM-MSCs, we found overloading BM-MSCs hindered the interaction between oocytes and ovarian somatic cells and inhibited follicle formation and development.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies have demonstrated promising results regarding the ability of MSCs to facilitate the regeneration of bone, blood vessels, skin, peripheral nerves, and alleviate symptoms of local ischemia in various organs like the heart, kidneys, and brain, it is important to note that MSCs have been sometimes viewed as a panacea within the field of tissue repair and regenerative medicine [ 24 , 36 ]. Studies also showed that co-cultured of MSCs with follicles could promote follicle survival and development [ 30 , 31 , 37 ]. In the study, when we tried to reconstitute the ovarian structure with different concentrations of BM-MSCs, we found overloading BM-MSCs hindered the interaction between oocytes and ovarian somatic cells and inhibited follicle formation and development.…”
Section: Discussionmentioning
confidence: 99%
“…Although previous studies on MSCs have shown surprising results in their ability to promote the regeneration of bone, blood vessels, skin, and peripheral nerves, as well as to improve the symptoms of local ischemia in a variety of organs, including heart, kidneys, and brain, MSCs have been regarded as a "cure-all" in the eld of tissue repair and regenerative medicine [24,34]. Studies also showed that co-cultured of MSCs with follicles could promote follicle survival and development [30,31,35]. In the study, when we tried to reconstitute the ovarian structure with different concentrations of BM-MSCs, we found overloading BM-MSCs hindered the interaction between oocytes and ovarian somatic cells and inhibited follicle formation and development.…”
Section: Discussionmentioning
confidence: 99%
“…The results of animal models have been applied to clinical practice, and transplantation of bone marrow MSCs from patients for repairing the damaged endometrium can restore the uterus to its normal function at conception [26]. The study of MSCs applied to improve ovarian function shows that MSCs can signi cantly improve the internal environment of the ovary in premature ovarian failure mice [27][28][29][30][31]. Although the above studies have demonstrated the role of MSCs in restoring or protecting ovarian function, most researchers believe that this is related to the regulation of factors secreted by MSCs, and whether MSCs differentiate into intraovarian cells has not been mentioned, it needs to be further investigated the mechanism of their role in the reconstruction of ovarian function.…”
Section: Introductionmentioning
confidence: 99%
“…The good safety profle of MSCs have been demonstrated in different clinical applications, such as infertility. Although the limited small sample trials indicated the safty of MSCs for more than a year in POI women, but long-term safety and adverse events are limited [ 173 ]. Therefore, further comprehensive and larger clinical studies are critical to establish the standardizing the preparation and ensuring the safety of the MSCs stherapy on the reproductive system [ 174 ].…”
Section: Clinical Applications Of Mscs In Poi Patientsmentioning
confidence: 99%